1990
DOI: 10.1002/arch.940130303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of teratocyte functions: An overview

Abstract: Teratocytes, derived from extra-embryonic tissues of parasitic Braconidae, Trichogrammatidae, and Scelionidae, play several important roles in the parasitoid-host interaction. It is clear from the literature that the specific roleb) vary among species. Only recently have the biochemical and endocrinological roles of these cells been considered. This overview examines the recent literature o n teratocytes and stresses the importance of in vitro procedures to elucidate the functional roles (trophic, immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 42 publications
0
37
0
2
Order By: Relevance
“…The third is the fragility of the particles in the standard buffers, salts, detergents and fixatives used for virus purification. This fragility may be caused by the proteases present in the parasitized nymphs and secreted by the wasp larvae and their teratocytes during development (Dahlman, 1990). However, the purified particles remain infectious, so it is likely that plating particles onto the carbon grids used for TEM might also cause some degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The third is the fragility of the particles in the standard buffers, salts, detergents and fixatives used for virus purification. This fragility may be caused by the proteases present in the parasitized nymphs and secreted by the wasp larvae and their teratocytes during development (Dahlman, 1990). However, the purified particles remain infectious, so it is likely that plating particles onto the carbon grids used for TEM might also cause some degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Although in some hymenopteran parasitoids teratocytes may have functions other than parasitoid nutrition (e.g. host immunosupression, host growth regulation) (Dahlman 1990 ), it was found by Ogloblin (1924) that in D. coccinellae the major function of teratocytes is to provide food for the developing parasitoid larva. More recently, characterized a specifi c polypeptide synthesized by the teratocytes from amino acids absorbed from the host haemolymph.…”
Section: Larval N Utritionmentioning
confidence: 99%
“…These cells are liberated into the host hemolymph when the parasitoid larva hatches [ l l ] and have been suggested to play trophic, immunosuppressive, and secretory roles [12,13]. In a previous study [14], we found that pupation was prevented when nonparasitized Heliothis virescens larvae were injected with Microplitis croceipes teratocytes.…”
Section: Introductionmentioning
confidence: 96%